Praxelis (Asteraceae: Eupatorieae), A Newly Naturalised Genus for Kalimantan and Sumatra, Indonesia - Hariri, Muhammad Rifqi; Irsyam, Arifin Surya Dwipa; Lestari, Ria Windi; Peniwidiyanti, Peniwidiyanti; Rahmaningtiyas, Lutfi; Zulkarnaen, Rizmoon Nurul; Widjaya, Aulia Hasan; Saripudin, Saripudin; Latifah, Dian; Yuliyanto, Ponco; Budianti, Noviana; Suhaya, Yoyo; Rosleine, Dian; Sulistyawati, Endah (Universitas Gadjah Mada, 2024)
The southern American genus Praxelis Cass. has 18 species. In Singapore and Indonesia, notably Java, P. clematidea R.M.King & H.Rob. has naturalised. The first record in Indonesia was in Bogor in 2018, although it is unverified elsewhere. Praxelis clematidea was found in Bangka, Belitung, Jambi, Lampung, and Palangka Raya during our exploratory field research in 2020–2023. The naturalised populations proliferate in roadsides, ditches, open spaces, and disturbed areas. It thrives in a small swampy peat environment in Palangka Raya. Praxelis clematidea has been found outside Java, suggesting it could become an invasive alien species in Kalimantan and Sumatra.